Differential effects of press vs. pulse seawater intrusion on microbial communities of a tidal freshwater marsh. Issue 1 (7th November 2020) - Mobilian, Courtney; Wisnoski, Nathan I.; Lennon, Jay T.; Alber, Merryl; Widney, Sarah; Craft, Christopher B.
Abstract: Tidal freshwater marshes (TFMs) are threatened by seawater intrusion, which can affect microbial communities and alter biogeochemical processes. Here, we report on a long‐term, large‐scale manipulative field experiment that investigated continuous (press) and episodic (pulse, 2 months/yr) inputs of brackish water on microbial communities in a TFM. After 2.5 yr, microbial diversity was lower in press treatments than in control (untreated) plots whereas diversity in pulse plots was unaffected by brackish water additions. Sulfate reducer abundance increased in response to both press and pulse treatments whereas methanogens did not differ among treatments. Our results, along with other lab and field measurements that show reduced soil respiration and extracellular enzyme activity suggest that continuous seawater intrusion will decrease macrophyte C inputs that reduce bacterial diversity in ways that also diminish ecosystem carbon cycling.